EFFECT OF NON-LINEAR DYNAMIC INTERACTION ON SECTIONAL FORCE OF BRIDGE PIERS SUBJECTED TO PULSELIKE GROUND MOTIONS - Inoue, T.; Nariyuki, Y. (Journal of Advanced Manufacturing Technology (JAMT), 2016)
In this study, we discuss the effects of uplift in spread foundation and yielding of underlying soils on the sectional force of bridge piers subjected to pulse-like ground motions. The effects could lead to reducing bridge damage caused by pulse-like ground motions. We simulated the pulse-like ground motions with sinusoidal pulse. We found that the sectional force of bridge piers subjected to the pulse-like ground motions was reduced by the uplift in spread foundation and the yielding of underlying soils. We also found that, regardless of the pulse acceleration amplitude, the sectional force was minimized, while the ratio Tp/Te of pulse period Tp to natural period Te was between 1 and 1.2, where the natural period Te was the primary natural period of the model that expressed the soil as an elastic body without considering the foundation uplift.